2019
DOI: 10.1002/cncr.31926
|View full text |Cite
|
Sign up to set email alerts
|

Impact of tumor, treatment, and access on outcomes in bladder cancer: Can equal access overcome race‐based differences in survival?

Abstract: BACKGROUND: There are race-based differences in bladder cancer survival. To better understand this phenomenon, this study was designed to assess the statistical contributions of tumor, treatment, and access variables to race-based differences in survival. METHODS: Data were extracted from the National Cancer Data Base on black and white adults with muscle-invasive bladder cancer from 2004 to 2015. The impact of tumor, access, and treatment variables on differences in survival was inferred by the performance of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 47 publications
0
14
0
Order By: Relevance
“…Finally, to quantify the relative contribution of stage at diagnosis and definitive treatment on the excess hazard of CSM in the uninsured, we compared the excess risk of death in insured and uninsured patients after each adjustment in all 6 cancers using a previously described method. [15][16][17][18] The individual contribution of stage and treatment on the excess risk of death in the uninsured is summarized in supplemental eTable 1 (available with this article at JNCCN.org).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, to quantify the relative contribution of stage at diagnosis and definitive treatment on the excess hazard of CSM in the uninsured, we compared the excess risk of death in insured and uninsured patients after each adjustment in all 6 cancers using a previously described method. [15][16][17][18] The individual contribution of stage and treatment on the excess risk of death in the uninsured is summarized in supplemental eTable 1 (available with this article at JNCCN.org).…”
Section: Resultsmentioning
confidence: 99%
“…Using a previously described approach, the change in the protective benefit of insurance was then compared after each adjustment and the relative change in excess risk of death among the uninsured was used to infer the contribution of stage at diagnosis and treatment of all 6 cancers. [15][16][17][18] For cancers with nonsignificant effect, a post hoc power analysis using a 2-sample comparison of exponential survivor functions was performed to estimate the achievable effect size using a b of 0.80 (corresponding to an acceptable false-negative rate of 20%) and an a of 0.01.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Recent studies focused on race-based differences in socioeconomic status (SES), quality of care, and treatment for individuals with bladder cancer have highlighted the considerable impact of nonclinical factors on access to quality care and receipt of standard, evidence-based treatment. 3,4 Although race and type of treatment have been shown to independently influence outcomes, how these two factors may interact to exacerbate racial disparities in bladder cancer is not well understood.…”
Section: Introductionmentioning
confidence: 99%
“…5 Recent studies have shown Black individuals with muscle-invasive bladder cancer (MIBC) have 21% lower odds of guideline-based treatment (GBT) and, in turn, GBT explained 35% of observed Black-White differences in survival, with an insignificant contribution from inherent tumor characteristics. 3,4 However, the effects of race and receipt of GBT may interact, resulting in nonadditive (multiplicative) effects. Extending this concept of intersectionality to describe the nonadditivity of microlevel factors such as race and SES with macrolevel factors such as health care implementation or quality of care delivery, is rarely explored.…”
Section: Introductionmentioning
confidence: 99%
“…Bladder cancer mortality is associated with environmental and socioeconomic factors such as race, region and gender [20]. A recent study by Cole et al [21] using a novel statistical modeling approach showed that eliminating disparities in access and treatment of MBIC results in essentially the same OS. These results have an enormous relevance for policy makers since it suggests that improving equity in access can reduce the impact of tumor characteristics in outcomes of patients with MIBC.…”
Section: Neoadjuvant Chemotherapy Use In Mibcmentioning
confidence: 99%